EFEK INFUSA DAUN SIRSAK (Annona muricata L.) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIBEBANI GLUKOSA - ., Chaiyathullah Asmonie (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Diabetes Mellitus causes patophysiological changes in multiple organs that can decrease quality of life and increase risk of morbidity and mortality. The management of diabetes is a global problem until now and successful treatment is not yet discovered. Soursop leaves (Annona muricata L.), empirically, has been used as antidiabetic agent. Objective. To determine the effect of soursop leaves infusion on blood glucose levels of wistar strain white male (Rattus norvegicus) rats with glucose pre-load. Method. This was an experimental study with controlled time series design and using oral glucose tolerance test. Glucometer easy touch was used in determining blood glucose level. This study used 25 white male wistar rats weighing 150-250 grams, and aged around 1.5-3 months old which were divided randomly into 5 groups: negative control group (aquades), positive control group (Metformin 63 mg/kgBW), soursop leaves infusion with dose 1 (25,2 mg / kgBW), dose 2 (50,4 mg/kgBW), and dose 3 (100,8 mg/kgBW). Result. This study shows that there are significant differences beetween dose 1 and negative control group (p=0,000), dose 2 and negative control group (p=0,000), dose 3 and negative control group (p=0,000), dose 1 and positive control group (p=0,000), and also dose 2 and positive control group (p=0,000). Conclusion. Soursop leaves infusion dose 1, dose 2 and dose 3 effective (p <0.05) in lowering blood glucose levels of white male wistar rats with glucose pre-load. Keywords: blood glucose levels infusion soursop leaves (Annoana muricata L.) glucose preload 1) Medical School, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo 2) Study Program of Pharmacy, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo 3) Department of Nutrition, Medical School, Faculty of Medicine, Tanjungpura University, Pontianak, West Borneo